1975
DOI: 10.1159/000178674
|View full text |Cite
|
Sign up to set email alerts
|

Impaired <sup>3</sup>H-Testosterone Uptake and Metabolism in the Accessory Sex Glands of Diabetic Castrated Male Rats

Abstract: The uptake and retention of 1, 2-3H-testosterone in accessory sex glands, muscle and liver of streptozotocin diabetic castrated male rats, insulin-treated diabetic castrated rats and non-diabetic castrated control rats were studied at various time intervals after an intravenous injection. Diabetes reduced the retention of 3H-testosterone in the prostate, the preputial gland and the epididymis. Exogenous insulin slightly increased the retention of 3H-testosterone in these tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…It is therefore suggested that the diabetes‐induced impairment in the availability of testosterone at the level of ventral prostate and its conversion to dihydrotestosterone (DHT) may be responsible for the histological changes recorded in the present study. Further, STZ‐diabetes in adult rats has been shown to reduce androgen receptor content (Tesone et al,1986) and uptake and retention of 3 H‐testosterone in accessory sex glands (Oksanen and Tuohimaa,1975). Therefore, the observed adverse effects in ventral prostate may also be due to the impaired binding of androgen to its receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore suggested that the diabetes‐induced impairment in the availability of testosterone at the level of ventral prostate and its conversion to dihydrotestosterone (DHT) may be responsible for the histological changes recorded in the present study. Further, STZ‐diabetes in adult rats has been shown to reduce androgen receptor content (Tesone et al,1986) and uptake and retention of 3 H‐testosterone in accessory sex glands (Oksanen and Tuohimaa,1975). Therefore, the observed adverse effects in ventral prostate may also be due to the impaired binding of androgen to its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Though the adverse effects of diabetes on testicular functions are well established (Handelsman et al,1985; Murray et al,1985; Sudha et al,1999), there is relatively less information on the impact of diabetes on the accessory sex organs (Oksanen and Tuohimaa,1975; Balasubramanian et al,1991), which contribute a major portion of seminal plasma (Brandes,1974; Marker et al,2003). Prostate, an androgen‐dependent accessory sex organ, secretes a complex mixture of nutrients in seminal fluid, which are essential for sperm viability, motility, and fertilizing capacity (Brandes,1974; Cunha et al,1987; Lee,1997).…”
mentioning
confidence: 99%
“…The mechanism of how hyperglycemia may affect · 1A -AR gene expression is not clear. In an earlier report, Oksanen and Tuohimaa [31] demonstrated reduced testosterone transformation to dihydrotestosterone in the prostate of diabetic rats. Whether neuroendocrine interaction plays an important part needs further investigations.…”
Section: Discussionmentioning
confidence: 85%
“…2,3 Streptozotocin (STZ)-diabetes in adult rats has been shown to reduce the androgen receptor content, 4 uptake and retention of [3H]testosterone in accessory sex glands. 5 Earlier reports from the author's laboratory [6][7][8] and others 9,10 have shown decreased synthesis and availability of testosterone in STZ-induced diabetic rats. Induction of diabetes causes a signicant reduction in the prostatic weight and serum testosterone level in rats.…”
Section: Introductionmentioning
confidence: 98%